Co-trimoxazole and prevention of relapses of PR3-ANCA positive vasculitis with pulmonary involvement - Zycinska, K (BioMed Central, 2009)
BACKGROUND: Bacterial and viral respiratory tract infections may trigger relapses in patients with PR3-positive vasculitis. Data have suggested that treatment with co-trimoxazole may be beneficial, because this antibiotic could act by eliminating the offending microbe and thereby stopping the initiating stimulus. GOAL AND METHODS: Prospective, randomized, placebocontrolled study of the efficacy of co-trimoxazole given 960 mg thrice weekly for 18 months in preventing relapses in patients with Wegener's granulomatosis (WG) in remission, after treatment with cyclophosphamide and prednisolone was conducted. Relapses and infections were assessed with predefined criteria based on clinical, laboratory, serological, microbiological, and histopathological findings. Sixteen patients were assigned to receive co-trimoxazole and 15 to receive placebo. RESULTS: Seventy five percent of the patients in the co-trimoxazole group remained in remission at 18 months and 55% of those in the placebo group. A proportional hazard regression analysis identified a positive PR3-ANCA test at the start of treatment, chronic nasal crusting, and Staphylococus aureus infection as risk factors for relapse. Furthermore, the analysis identified treatment with co-trimoxazole as an independent factor associated with prolonged diseasefree interval. CONCLUSION: Treatment with co-trimoxazole reduces the incidence of relapses in patients with Wegener's granulomatosis in remission.